DEVELOPMENT OF A MANUALLY OPERATED RICE TRANSPLANTER USING FOUR-BAR LINKAGE MECHANISM - RANJAN KUMAR NIRALA; UTTAM KUMAR* (The Journal of Research ANGRAU, 2020)
The manually operated two-row rice transplanter was developed to transplant root washed type seedlings using four bar linkage transplanting mechanism during 2016. Effective field capacity of the transplanter was 0.012 ha h-1 at an operating speed of 0.36 km h-1. The average height of the seedlings were 162.2 mm, 190.35 mm and 220.55 mm for 20, 25 and 30 days old seedlings, respectively.Average hill-to-hill spacing, number of seedlings per hill and depth of planting were 200.22 mm, 4.06 mm and 61.66 mm, respectively. Average missing hills, floating hills and visible damage of the transplanter were10.33%, 6.17% and 2.83%, respectively.Cost of transplanting by the transplanter was Rs.6500 ha-1, whereas, by manual transplanting it was Rs.11400 ha-1, thus,there is a saving of Rs.4900 ha-1.